The impact of thyroid autoimmunity on pregnancy outcomes in women with unexplained infertility undergoing intrauterine insemination: a retrospective single-center cohort study and meta-analysis - Li, Jiaxu; Yu, Jiaxin; Huang, Yingqin; Xie, Baoli; Hu, Qianwen; Ma, Nana; Qin, Rongyan; Luo, Jianxin; Wu, Hao; Liao, Ming; Qin, Aiping (Frontiers in Endocrinology, 2024)
Results regarding the effect of thyroid autoimmunity (TAI) on pregnancy outcomes remain controversial. There is limited research on the effect of TAI on the treatment outcome of intrauterine insemination (IUI). This study aimed to assess whether TAI is associated with different pregnancy outcomes in women with normal thyroid function who are treated with IUI for unexplained infertility (UI). Our retrospective cohort study included 225 women with unexplained infertility who received 542 cycles of IUI treatment. Patients were divided into the TAI+ group (N=47, N=120 cycles) or TAI- group (N=178, N=422 cycles). We conducted systematic reviews and meta-analyses. Comparison of pregnancy outcomes based on TAI status showed that the clinical pregnancy rate (odds ratio [OR]: 0.43, P=0.028, 95% confidence interval [95%CI]: 0.20-0.93) and live birth rate (OR: 0.20, P=0.014, 95%CI: 0.05-0.71) were significantly lower in the TAI+ group than in the TAI- group. There was no significant difference in pregnancy rate between the groups (OR: 0.61, P=0.135, 95%CI: 0.32-1.17). In the systematic review and meta-analysis, two studies from the establishment of the database until June 2023 were included and this original retrospective study was added to include 3428 IUI treatment cycles. Clinical pregnancy rates (OR: 0.77, P=0.18, 95%CI: 0.53-1.13) and live birth rates (OR: 0.68, P=0.64, 95%CI: 0.13-3.47) were not statistically different between the groups. Our retrospective cohort study found that TAI is associated with reproductive outcomes in UI patients treated with IUI. However, when these findings were combined with other studies in a meta-analysis, no statistically significant association was observed. Our study highlights the need for caution when interpreting the relationship between TAI and reproductive outcomes. Future studies should consider a broader population and more rigorous study design and clinicians dealing with women with UI-TAI should be aware of the complexity of this field and the limitations of available evidence.